2019
DOI: 10.15537/smj.2019.2.23602
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the first and second mandibular molar roots proximity to the inferior alveolar canal and cortical plates using cone beam computed tomography among the Saudi population

Abstract: Objectives: To evaluate the relationship of the first and second mandibular molar roots to the inferior alveolar canal (IAC) and cortical plates using cone beam computed tomography (CBCT) in the Saudi population. Methods: Scans of 60 patients were collected retrospectively from the dental hospital database in King Saud University, Riyadh, Kingdom of Saudi Arabia. Measurements of the right and left first and second mandibular molars for each dental root and the mandibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
(33 reference statements)
3
15
0
1
Order By: Relevance
“… 26 The distance from buccal bone to the mesial and distal roots was found to be shortest in the Iranian population, whereas the distance from buccal bone to the distal root in the Turkish population was greatest among these populations. 4 , 5 , 26 These discrepancies are likely due to ethnic genetic differences, varying bone thicknesses, and distinctive topographical and anatomical relationships. 27 In all of these reports, the distance from the buccal bone to the distal root was longer than to the mesial root in two-rooted MFMs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“… 26 The distance from buccal bone to the mesial and distal roots was found to be shortest in the Iranian population, whereas the distance from buccal bone to the distal root in the Turkish population was greatest among these populations. 4 , 5 , 26 These discrepancies are likely due to ethnic genetic differences, varying bone thicknesses, and distinctive topographical and anatomical relationships. 27 In all of these reports, the distance from the buccal bone to the distal root was longer than to the mesial root in two-rooted MFMs.…”
Section: Discussionmentioning
confidence: 86%
“… 3 5 , 25 Few studies have evaluated the bony structures around MFMs in different populations. 4 , 5 , 26 In these studies, the distance from the buccal bone to each root at the resection level in two-rooted MFMs was reported in Iranian, Turkish, and Saudi populations. Our study evaluated the distance from the buccal bone to each root at the resection level for two-rooted and three-rooted MFMs.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent, consecutive 50 articles containing “inferior alveolar canal” or “inferior alveolar nerve canal” were included (defined as the IAC/IANC group) (Adibi, Shahidi, Nikanjam, Paknahad, & Ranjbar, 2017; Afsa & Rahmati, 2017; Al‐Ekrish et al, 2018; Al‐Ekrish et al, 2020; Ali, Mosleh, & Shawky, 2018; Aljarbou, Aldosimani, Althumairy, Alhezam, & Aldawsari, 2019; Arbel et al, 2019; Atef & Mounir, 2018; Česaitienė, Česaitis, Junevičius, & Venskutonis, 2017; Y. Chen, Liu, Pei, Liu, & Pan, 2018; Clark, Barbu, Lorean, Mijiritsky, & Levin, 2017; Demirel & Akbulut, 2020; Dutra et al, 2019; Elkhateeb & Awad, 2018; Ghai & Choudhury, 2018; Goller Bulut & Köse, 2018; Gumusok, Alkurt, Museyibov, & Ucok, 2016; He, Wang, Hu, & Liu, 2019; Ishii, Abe, Moro, Yokomizo, & Kobayashi, 2017; Kablan, Abu‐Sobeh, Lorean, & Levin, 2020; Khojastepour, Khaghaninejad, Hasanshahi, Forghani, & Ahrari, 2019; Kubota, Imai, Nakazawa, & Uzawa, 2020; S. Lee, Lee, Kim, & Nam, 2019; Liu, Sidell, Huon, & Torre, 2018; Luangchana, Pornprasertsuk‐Damrongsri, Kitisubkanchana, & Wongchuensoontorn, 2019; Mortazavi, Baharvand, & Rezaeifar, 2018; Mortazavi, Baharvand, Safi, & Behnaz, 2019; Mortazavi, Baharvand, Safi, Dalaie, et al, 2019; Patil, Pai, Vineetha, Rajagopal, & Dkhar, 2019; Patrick, Birur, Gurushanth, Raghavan, & Gurudath, 2017; Pour, Sedaghati, & Shamshiri, 2020; Prakash et al, 2018; Qi et al, 2019; Rytkönen & Ventä, 2018; Saha, Kedarnath, & Singh, 2019; Şahin, Odabaşı, Demiralp, Kurşun‐Çakmak, & Aliyev, 2019; Sharifi, Beshkar, Mobayeni, & Hasheminasab, 2018; Shokry et al, 2019; Sirin, Yildirimturk, Horasan, & Guven, 2020; Tabrizi et al, 2019; Tachinami, Tomihara, Fujiwara, Nakamori, & Noguchi, 2017; Tudtiam et al, 2019; Uchida, Motoyoshi, Namura, & Shimizu, 2017; Uzun, Sumer, & Sumer,…”
Section: Methodsmentioning
confidence: 99%
“…I have read with interest the study by Aljarbour et al1 The reported data are of high importance for dental practitioners who perform dental extractions, root canal treatments, and place dental implants on regular basis to avoid potential damage to the inferior alveolar nerve. However, several points have tracked my attention while reading this paper as follows:…”
mentioning
confidence: 99%